The Effect of Religiosity and Spirituality on Mental Health: Reply to Two Commentaries - Garssen, Albertus (The international journal for the psychology of religion, 2021)
We published a meta-analysis to determine the longitudinal positive effect of religion or spirituality (R/S) on mental health. Forty-eight longitudinal studies were summarized (59 independent samples). The meta-analysis yielded a significant, but small overall effect size of r =.08. We concluded that there is evidence for a positive effect of R/S on mental health, but this effect is small. Our meta-analysis was recently criticized in this Journal by Koenig et al. Scientific debate is welcome, but we disagree with most of their comments. Our reply focusses on the following topics: Is the effect of R/S small? Might methodological issues underlie the small overall effect size? Randomized controlled studies, and change course and look elsewhere for more convincing results?